Impact of enzyme treatment on flavour of aronia juice - Mari Sandell; Anita Vanag; Oskar Laaksonen (Austria, 2022)
Aronia (Aronia mitschurinii) is rich in different polyphenolic compounds and sorbitol. Pressed aronia juice has a beautiful colour. The aim of this work was to analyse smell and taste of aronia juices prepared from berries grown in South-West of Finland. Sensory properties were studied using projective mapping with consumers and applying qualitative profiling with experienced sensory panel. Sugar and acid composition was analysed with GC-FID. Based on our results, pectinase treatment had a negative impact on both odour and taste of aronia juice.
Flavour Science: Proceedings of the XV Weurman Flavour Research Symposium